Taxonomia polifásica e características proteômicas do complexo Sporothrix schenckii - Rodrigues, Anderson Messias [UNIFESP] (2010)
Sporotrichosis is a chronic mycotic infectious disease of man and animals caused by the traumatic implantation of a pathogenic fungus that typically involves the skin and subcutaneous tissue. Since 1898, when the sporotrichosis etiological agent was discovered by Schenck, this disease has been attributed to a single pathogen, Sporothrix schenckii Hektoen & Perkins, a thermo dimorphic fungus that grow as a yeast at 37 ºC and as a mycelium at room temperature. However, isolates identified as S. schenckii showed a great deal of genetic variability, suggesting that this taxon consist in a cryptic species complex. Based on this information our group is interested in the study of the polyphasic taxonomy of this species complex and its implication on its ecoepidemiology in Brazil. We studied 161 strains of Sporothrix spp. provided from environmental and clinical samples obtained from diverse regions of Brazil and other countries. The phenotypic parameters assayed include vegetative growth on PDA media at different temperatures (30, 35, 37 and 40 ºC), the colony colors on CMA media, the assimilation pattern of carbon sources (raffinose, ribitol and sucrose) and morphological microscopic features of in vitro cultivation. The phenotypic data were confirmed by molecular biology using the sequencing information of a fragment of calmodulin locus. Our data show that the S. brasiliensis, S. globosa, S. mexicana and S. schenckii have a widespread geographical distribution in Brazil. To our knowledgement this is the first description of the specie S. mexicana outside of Mexico and causing disease in human host. S. brasiliensis was isolated with high frequency from cats in Rio Grande do Sul and Rio de Janeiro states, suggesting that cats has been an important vector in epidemiology of this specie. A proteomic approach was proposed in this work to compare protein profile of Sporothrix spp. isolates and get a better understanding about the differences in terms of protein expression among the cryptic species. The 2-D profiles were strongly different among the isolates. To elucidate the major antigen of human sporotrichosis, the fungus was cultured in BHI broth, 37 °C, and intracellular proteins were resolved by 2-DE. Proteins were transferred to a nitrocellulose membrane and then incubated with serum from patients with the two major clinical form of disease (cutaneous fixed and linfocutaneous). Our results show that IgG present in serum from patients react with different antigens from Sporothrix schenckii complex. Immunoblotting showed that the sera of patients had antibodies reacting with a 70 kDa antigen in three isolates (S. brasiliensis, S. globosa and S. schenckii). Profile differences in antigenicity were observed between S. mexicana and the other species studied here.